Subtract to solve: a pilot study testing implicit and experiential interventions against additive bias - Neroni, Maria Adriana (Frontiers in Cognition, 2025)
When seeking to transform an object, idea, or situation, individuals often default to adding new components rather than removing existing ones, a cognitive tendency known as additive bias. Although recently formalized in cognitive science, strategies to mitigate this bias remain limited. This pilot study investigated the potential of the additive bias Implicit Association Test (ad-IAT) as a scalable educational tool for raising awareness of additive bias and promoting subtractive thinking. Sixty participants were randomly assigned to one of three conditions: ad-IAT, experiential learning, or control. In Session 1, all participants completed a familiarization task with a digital grid, which served as the foundation for the subsequent tasks in the study. In Session 2, participants completed either the ad-IAT (with personalized feedback), a grid-based experiential task emphasizing subtractive efficiency or an unrelated gender IAT. In Session 3, all participants completed the same test grid, structured so that symmetry could be achieved more efficiently through subtraction than addition. Results showed that participants in the ad-IAT condition exhibited a strong implicit preference for additive concepts. Although differences in strategy use were not statistically significant across conditions, both the ad-IAT and experience groups demonstrated higher accuracy than the control group, with the experience group completing the task significantly faster. These findings suggest that both implicit and experiential interventions can reduce reliance on additive strategies, with the ad-IAT offering a time-efficient and scalable method for promoting metacognitive insight and behavioral change. Implications for creativity, education, and cognitive training are discussed.